Analisis Pembelajaran Drama untuk Meningkatkan Kreativitas Mahasiswa dalam Penulisan Lakon Di Perguruan Tinggi - Noviea Varahdilah Sandi; Ririn Setyorini (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2019)
The aim of this research is to examine process of writing in act of drama, that doing by students in college. The write of script is for developing students creativity and knowledge in order to imagine in field of drama script writing.. Design in this research using qualitative, and the method using descriptive method, that will learn and describe learning of act writing as proponent the running of show in order to developing students creativity in field of dance and drama class. Subject of this research are students of VI semester that take dance and drama class in Peradaban University year of 2017/2018.The analysis technique used interactive model analysis. The results of this study showed that from several students involved in the PGSD1 and PGSD2 classes in making play scripts, only two students passed the selection, two play scripts which were chosen to be performed in dance and drama performances, while the results of this writing showed almost all students cannot develop ideas, experiences and pour creative thoughts into text.